Interpretasi Bawah Permukaan Berdasarkan Distribusi Nilai Tahanan Jenis di Daerah Puspiptek, Serpong - Karunianto, Adhika Junara; Haryanto, Dwi; Syaeful, Heri (EKSPLORIUM, 2018)
The area of Center for Research in Science and Technology (PUSPIPTEK) Serpong is 460 hectares wide. Most of the area is a Green Open Spaces (RTH). In the line with the growth of research activities, the need for infrastructure and building facilities also increases. As a national strategic facility, it is necessary to design buildings that are sturdy for and suitable with subsurface conditions. Geolectrical survey can be used to determine of subsurface condition/information. The purpose of this study is to obtain the ilustration of subsurface, based on the distribution of geoelectric resistivity values in the site of Experimental Power Reactor (RDE) construction. The resistivity data acquisition is using a multichannel resistivitymeter MAE X612EM+ type in 2-D by 48 channel of Wenner-Schlumberger configuration. The numbers of elctrodes used are 48 with an electrode interval of 5 m. Based on 2-D inversion model, there are four section models obtained, namely line-1, line 2, line-3, and line-4. The data error for each section is relatively small, less than 12%. Geological interpretation carried out in the section line-2 and line-3 illustrates the existence of layers A, B, and C. Layer A is interpreted as rock with silt to clay grain size containing organic material with resistivity values range 2-20 ohm-m and thickness varries in 1-7 m. Layer B is interpreted as sandstone which has a range of resistivity values from 10-90 ohm-m with thickness variations 5-20 m. Layer C is interpreted as claystone which has a range of resistivity values from 2-5000 ohm-m with depth variation in 10-20 m.